Impact Of Digital Technostress On Interest In Using Fintech E-Wallets Among Generation Z Consumers In Lampung Province - Gayuh Rizki Utomo; Endang Asliana; Lihan Rini Puspo Wijaya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out how digital technostress influences interest in using fintech e-wallets among millennial generation consumers in Lampung Province. The population in this research is generation Z consumers in Lampung Province. The sampling technique was carried out using purposive sampling. Data collection in this study was carried out by distributing questionnaires to 100 respondents. The method used in this research is quantitative research and uses primary data. In this research there are four independent variables, namely complexity, overload, invasion, and uncertainty, while the dependent variable used is intention. This study uses multiple linear regression analysis tools with the help of the SPSS version 23 program. The results of the research show that complexity and overload have a positive and significant effect on interest in using fintech e-wallets among generation Z consumers in Lampung Province, whereas invasion and uncertainty have no effect on interest in using fintech e-wallets. Fintech e-wallet for generation Z consumers in Lampung Province.